From body motion to cheers: Speakers' body movements as predictors of applause. (February 2015) - Koppensteiner, Markus; Stephan, Pia; Jäschke, Johannes Paul Michael
Highlights: Stick-figure animations of speakers were rated on different personality traits. Ratings were related to the applause and the hecklings the speakers received. Dominance, agreeableness and extraversion were notable predictors of applause. People read socially relevant information from body motion. Abstract: Appearance cues and brief displays of behavior are related to people's personality, to their performance at work and to the outcomes of elections. Thus, people present themselves to others on different communication channels, while their interaction partners form first impressions on the basis of the displayed cues. In the current study we examined whether people are able to read information from politicians' body motion. For a rating experiment we translated short video clips of politicians giving a speech into animated stick-figures and had these animations rated on trustworthiness, dominance, competence and the Big Five personality dimensions. Afterwards we correlated the ratings with the applause and the hecklings that the speakers received throughout their entire speech. This revealed that speakers whose body movements were perceived as high on dominance, as high on extraversion and as low on agreeableness received more applause. Although the results obtained need support from additional studies they indicate that body motion is an informative cue in real life settings.